Editorial for the Special Issue “Gut Dysbiosis: Molecular Mechanisms and Therapies 2.0” - Carmine Stolfi; Federica Laudisi (Biomedicines, 2024)
Gut homeostasis depends on maintaining a fine equilibrium between the intestinal epithelial barrier, the microbiota, and the host’s immune system [...]